Comparative Evaluation between Self-Assembling Peptide P11-4 and ACP CPP in Enamel Remineralization Post Er:YAG Laser Irradiation - A Confocal Laser Scanning Microscopic Study - H. Bhargavi; Savitha B. Naik; N. Kiran Kumar; Seema Merwade; Biji Brigit; Shriya Sunil Bhumralkar; Ashwini Suresh Kadam; H. S. Preetham (Contemporary Clinical Dentistry)
Background: The focus in caries management has shifted to early detection of caries lesions and targeted noninvasive management of incipient lesions using novel remineralizing agents. Aim and Objective: The study aimed to compare and evaluate the remineralization potential of self-assembling peptide (Curodont repair) and ACP-CPP (MI varnish) on human enamel and to compare and evaluate the effect of Er:YAG laser on their remineralizing potential. Materials and Methods: A total of 36 teeth were divided into four experimental groups after etching all the specimens with 36% phosphoric acid to create an artificial white spot lesion (WSL). Demineralization depth was analyzed using confocal laser scanning microscope and samples were divided into four groups; Group 1 and Group 2 specimens were treated with remineralizing agents ACP-CPP and self-assembling peptide, whereas Group 3 was treated with Er:YAG laser and ACP–CPP and Group 4 specimens received Er:YAG laser and self-assembling peptide. The remineralizing pastes were applied with applicator tips and left on for 2 min, laser activation was done with an energy of 100 mJ, frequency of 10 Hz, and with the use of minimum air/water spray following which the samples were thoroughly washed with deionized water and stored in artificial saliva. The same procedure is carried out for 14 days. After the procedure, all the enamel samples were assessed for confocal laser scanning microscopy. Results: The depth of remineralization was significantly increased in all four groups as compared to the depth of demineralization, but the mean difference was significantly highest in Group 4, Group 3, and Group 2, and least in Group 1. Conclusion: In this study, the most effective method for increasing the remineralization of the WSLs was the simultaneous use of the Er:YAG laser and self-assembling peptide together. The better results observed in Group 4 might be due to the synergistic effect of laser and self-assembling peptide.